Comparison between the use of 99% ethanol and 3% polidocanol in percutaneous echoguided sclerotherapy treatment of simple renal cysts - Dell’Atti, Lucio (Urol Ann, 2015)
AIM: In this study, we compared and valued efficacy and safety of percutaneous echoguided sclerotherapy (PES) using 3% polidocanol with that using 99% ethanol in the treatment of patients with simple renal cysts. MATERIALS AND METHODS: PES was performed for 65 simple renal cysts. Under ultrasonographic guidance the cyst was punctured using an 18 gauge needle. Sclerotherapy was performed with ethanol in 55% (36/65) of cases and with polidocanol in the remaining 45% (29/65). Patients were followed up with an ultrasound examination at 4 months, 8 months, and then at yearly intervals. A reduction of 50% or greater in cyst diameter was considered successful. RESULTS: The median followup period for the ethanol and polidocanol groups was 24.6 and 22.8 months, respectively. The successful outcome ratio of the polidocanol group was significantly higher (90% vs. 61%, respectively) than the one of the ethanol group (P = 0.003). The partial regression of the ethanol and polidocanol groups were 6% versus 7%, respectively. The failure ratio of the polidocanol group was significantly lower (3% vs. 33%, respectively) than that of the ethanol group (P = 0.004). Neither infectious complications nor hyperthermia occurred in all treated cases. However, these methods are not completely free from symptoms. All these symptoms disappeared few hours after the procedure. CONCLUSIONS: Polidocanol is a safe and effective sclerosing agent for renal cysts, with superior clinical results than ethanol. Therefore, polidocanol can be an alternative to ethanol in sclerotherapy of renal cysts.